PENGARUH KUALITAS SDM, KOMITMEN ORGANISASI DAN PENGGUNAAN TEKNOLOGI SIA PADA KINERJA AUDITOR - Ardiansyah, Rendi; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of characteristic of government institution which is proxy bythe quality of human resources, organization commitment and the effectiveness ofthe use of accountinginformation system technology on auditor performance. This research is conducted in Surabaya Inspectorate.The samples of this research have been obtained by using purposive sampling method to the employee ofSurabaya Inspectorate and based on predetermined criteria 37 auditors have been selected as samples. Theanalysis method has been carried out by using multiple linear regressions. The result of this research shows that:(1) human resources gives positive influence to the auditor performance, because the Surabaya Inspectorate hasrun the regulations of SPKN (State Financial Audit Standard) it has been proven that the minimum educationalbackground of auditors is bachelor degree / under graduates (S1) and the auditor has achieved relevant training.(2) Organization commitment does not give any influence to the auditor performance because the auditors hasweaknesses in conducting oversight in thepreparation and planning process. (3) The effectiveness of the use ofaccounting information system technology gives positive influence to the auditor performance because theauditors of Surabaya Inspectorate can use and take the advantage of the accounting information system throughsoftware or computerized accounting program therefore it can ease their tasksof as the government internaloversight.Keywords: Human resources, organization commitment, the effectiveness of the use of accounting informationsystem technology, auditor performance.